2020
DOI: 10.3390/antiox9020109
|View full text |Cite
|
Sign up to set email alerts
|

Pechiche (Vitex cymosa Berteo ex Speng), a Nontraditional Fruit from Ecuador, is a Dietary Source of Phenolic Acids and Nutrient Minerals, in Addition to Efficiently Counteracting the Oxidative-Induced Damage in Human Dermal Fibroblasts

Abstract: Pechiche fruits (Vitex cymosa Berteo ex Speng) from Ecuador were studied to determine their phenolic acid profile, nutrient minerals and capacity to protect primary human dermal fibroblasts (HDFa) against oxidative-induced damage. Up to five phenolic acids were identified, with homovanillic acid as the main one. Vitamin C, β-carotene and lutein were also determined. Phosphorus and potassium were the main macrominerals, while iron was the principal micromineral. HDFa were preincubated with a crude pechiche extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…However, the fruit is rich regarding micronutrients, potassium (287.8 mg/100 g), phosphorous (21.1 mg/100 g), and iron (0.43 mg/100 g), as well as vitamin C for children of 1-3 years of age and a source of fiber for children and adults (Caldeira et al 2004). That was corroborated by results of fruits analyzed in Ecuador, showing that phosphorous and potassium were the main macro-minerals found in natura fruits (Guevara et al 2020).…”
Section: Nutritional Composition Datasupporting
confidence: 68%
“…However, the fruit is rich regarding micronutrients, potassium (287.8 mg/100 g), phosphorous (21.1 mg/100 g), and iron (0.43 mg/100 g), as well as vitamin C for children of 1-3 years of age and a source of fiber for children and adults (Caldeira et al 2004). That was corroborated by results of fruits analyzed in Ecuador, showing that phosphorous and potassium were the main macro-minerals found in natura fruits (Guevara et al 2020).…”
Section: Nutritional Composition Datasupporting
confidence: 68%
“…Research has demonstrated a significant positive relationship between higher potassium consumption and a reduced risk of coronary heart disease and stroke. Conversely, insufficient potassium intake and excessive sodium consumption have been linked to the development of cardiovascular disease [5]. To mitigate the risk of hypertension, cardiovascular disease, stroke, and coronary heart disease, the World Health Organization recommends that adults increase their daily potassium intake to 3.5 g [6].…”
Section: Introductionmentioning
confidence: 99%